An accumulated wrong: Roger Casement and the anticolonial moments within imperial governance. (April 2019) - Kearns, Gerry; Nally, David
Abstract: Taking three moments of governance – executive, legislative and judicial – this paper explains how forms of anticolonial critique were composed and articulated within the general regime of imperial rule. Through the career of Roger Casement, this paper shows how international human rights could develop out of the administration of empires as they monitored and compared the treatment of their own subjects in other imperial spaces. Casement drew particularly on his Irish heritage to identify the expropriation of direct producers as the basis of colonial rule. For Casement, colonialism was coeval with the destruction of native life. This was a far more systematic critique than was typical in commentary on the evils of colonialism. It finally impelled Casement into open rebellion, giving him one last opportunity – from the dock as a convicted traitor – to make public an anticolonial epistemology that challenged the legitimacy of imperial sovereignty. Highlights: Uses the example of Roger Casement to examine geographies of anticolonialism. Demonstrates how anti-colonial ideas developed within imperial governance. Argues that Casement evolved a systematic theory of colonialism. Shows Casement's solidarity with people under colonialism regardless of race. Proposes that Casement's solidarity produced a global conception of human rights.